Pengaruh Perputaran Persediaan Terhadap Likuiditas Pada PT Indofood Tbk dan PT Mandom Tbk - Achmad, Daniel Noor; Magdalena, Annaria; Wijaya, Frans (Jurnal Ilmiah Manajemen Kesatuan, 2014)
Inventory is very important especially as building blocks for companies in producing a product will be sold. Whereas production process defines assessment of liquidity level crucial to the company 's ability to pay its short-term debts at maturity. Based on the graphic of the INTO movement, Current, Cash, Quick Ratio we can see the relationship benveen invent.ory tumover (INTO) with liquidity (Cash Ratio, Quick Ratio and Current Ratio) of PT Indofood Tbk in 2007 until the year 2009 showed that when inventory turnaround went slow, the company 's liquidity would decrease. And on the contrary, the company's liquidity would increase when the inventory tumaround was fast. In 2010 and 2011 showed a decreased inventory turnover but increased liquidity, this is due to the presence ofotherfactors influencing company 's liquidity such as the management of the company's most liquid current assets. Overall, inventory tumaround at PT. Mandom, Tbk on every year in the period 2007 to 2011 are fluctuating. This can be seen from the increasing and decreasing value of the company. We can still say that PT. Mandom Tbk still holds consumer preferences, and can still fulfil consumers ' demands, and being innovative at the same time. Qualitatively, the company experienced a slower performance but managed to slowly get into performance again. For 5 years, 2010 is the year when the company experienced the highest inventory turnover achieved as much as 4.78 times, and 2008 was the lowest inventory turnover as much as 3.42. Keywords: INTO and LIQUIDTY